12. Isolate Of Bacteriua Cellulase Enzyme Production In The Rumen Of Aceh Cattle Base On Analysis Homology 16S rRNA - Indah Melzana; Safika Safika; Darmawi Darmawi; Erina Erina; Fakhrurrazi Fakhrurrazi; Al Azhar (Jurnal Medika Veterinaria, 2020)
The rumen of cattle is well known one of a bacterium cellulolitic production that have ability to degrade cellulose for produce cellulase enzymes. The aims of the present study is to determine the type of bacteria produced cellulase enzymes in the rumen of cattle aceh. The diversity of cellulolitic bacteria is determined by  analysis of 16S rRNA genes. Isolation of cellulolytic bacteria, total DNA isolation, agarose gel electrophoresis, amplification of the 16S rRNA gene, determining the DNA sequence, DNA sequence homology and alignment of DNA sequences. Isolation of bacterium cellulolitic, isolating total DNA, gel electroforesis agarosa, amplified of gen 16S rRNA, determination the DNA barcode,  homology DNA barcode, and alignment of DNA sequences. The sample of rumen liquid was taked from RPH , then maked isolation of total DNA to get pure DNA from bacterium whos result and amplification DNA of bacterium cellulolitic separated by electroforesis gel agarosa. Gene of bacterium cellulolitic was isolated based Polymerase Chain Reaction methode. Alignment is done by using BlastN program, then use CLustalW program.  It can be concluded that the species of bacteria (FKH_USK_6) in rumen has a closeness with Coronabacter sakazakii bacteria strain PNP8 of 97% according to the sizeof the DNA sequence and the same position on an existing gene in GenBank.